Risk factors associated with hypertension among inmates in southern Brazil - Alexandre Inácio Ramos; Mateus Rodrigo Palombit; Kassiano Carlos Sinski; Ronaldo Luchesi Maciel; Rafaela Azevedo Abrantes de Oliveira Simoneti; Erica de Brito Pitilin; Marcela Martins Furlan de Léo; Jeferson Santos Araújo; Vander Monteiro da Conceição (Universidad Nacional de Colombia, 2022)
Objective: To identify the association between risk factors for systemic arterial hypertension and blood pressure levels in prisoners under a closed regime. Materials and methods: Cross-sectional study conducted with prisoners under a closed regime between February and September 2019. A total of 240 men from a penitentiary complex in southern Brazil participated in the study. A semi-structured instrument based on the national guidelines for cardiovascular diseases was used for data collection. Results: Univariate analysis allowed us to identify that physical exercise was negatively associated with the development of systemic arterial hypertension (p = 0.034). However, body mass index and abdominal circumference were positively associated with cardiovascular risk and systemic arterial hypertension (p = 0.000). Through multivariate analysis, we noted the statistical significance of the body mass index when controlled for all other variables in the model (adjusted OR = 2.33). Conclusions: Risk factors for the development of systemic arterial hypertension are present in the prison environment to a similar degree as in the general population; particularly the absence of physical exercise and altered body mass index and abdominal circumference. It is worth mentioning that the body mass index was the variable of greater statistical significance, since, when altered, it increased 2.33 times the chance of inmates to develop systemic arterial hypertension.